2008
DOI: 10.1128/cvi.00070-08
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Host Interleukin-10 Polymorphisms on Development of Traveler's Diarrhea Due to Heat-Labile Enterotoxin-ProducingEscherichia coliin Travelers from the United States Who Are Visiting Mexico

Abstract: Up to 60% of U.S. visitors to Mexico develop traveler's diarrhea (TD), mostly due to enterotoxigenicEscherichia coli (ETEC) strains that produce heat-labile (LT) and/or heat-stable (ST) enterotoxins. Distinct single-nucleotide polymorphisms (SNPs) within the interleukin-10 (IL-10) promoter have been associated with high, intermediate, or low production of IL-10. We conducted a prospective study to investigate the association of SNPs in the IL-10 promoter and the occurrence of TD in ETEC LT-exposed travelers. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
11
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 28 publications
3
11
0
1
Order By: Relevance
“…High levels of IL-10 in our study appear to be inadequate in resolving ETEC infections. This result is consistent with findings that LT-ETEC-infected individuals with IL-10 alleles associated with high IL-10 produc- tion had a limited ability to rapidly clear infection (12). These findings suggest that the antiinflammatory effects of high levels of IL-10 inhibit the clearance of ETEC infections.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…High levels of IL-10 in our study appear to be inadequate in resolving ETEC infections. This result is consistent with findings that LT-ETEC-infected individuals with IL-10 alleles associated with high IL-10 produc- tion had a limited ability to rapidly clear infection (12). These findings suggest that the antiinflammatory effects of high levels of IL-10 inhibit the clearance of ETEC infections.…”
Section: Discussionsupporting
confidence: 82%
“…Recent research has reported that distinct cytokine pathways are involved in the host responses to each of these enteropathogens (12,21). These findings suggest that a specific cytokine response adequate for resolving one pathogen infection may be inappropriate against a different pathogen and so lead to prolonged infection and pathogenesis.…”
mentioning
confidence: 99%
“…In line with this, recent studies have shown that both genetic predisposition (9,14) and nutritional status (17,18,30) increase the probability of a DEP diarrhea episode.…”
Section: Discussionsupporting
confidence: 48%
“…Incomplete protection against ETEC is also seen in the face of preexisting, low-level anti-LT immu-VOL. 77,2009 MINIREVIEW 5211 on May 9, 2018 by guest http://iai.asm.org/ nity in travelers, who must also have naturally induced anti-LT antibodies (22). Toxin and other ETEC antigen antibody responses derived from natural protection and vaccines wane over time (10,90), data reinforced by the cholera-like ETEC disease seen in Bangladeshi adults (73).…”
Section: Naturally Induced Toxin Immunitymentioning
confidence: 97%